2014
DOI: 10.1002/adfm.201400960
|View full text |Cite
|
Sign up to set email alerts
|

Towards van der Waals Epitaxial Growth of GaAs on Si using a Graphene Buffer Layer

Abstract: Van der Waals growth of GaAs on silicon using a two‐dimensional layered material, graphene, as a lattice mismatch/thermal expansion coefficient mismatch relieving buffer layer is presented. Two‐dimensional growth of GaAs thin films on graphene is a potential route towards heteroepitaxial integration of GaAs on silicon in the developing field of silicon photonics. Hetero‐layered GaAs is deposited by molecular beam epitaxy on graphene/silicon at growth temperatures ranging from 350 °C to 600 °C under a constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 40 publications
(40 reference statements)
3
126
0
Order By: Relevance
“…[1][2][3][4] In addition, 2D materials such as graphene, boron nitride nanosheets, and layered transition metal dichalcogenides (TMDs) were investigated as potential buffer layers for the epitaxial growth of III-V semiconductors on foreign substrates. [5][6][7][8] The use of TMDs, in particular, layered-MoS 2 as a buffer layer attracts the potential interest of researchers to address the issues such as large lattice and thermal expansion mismatch for the growth of GaN. 9,10 Recently, GaN epitaxy on layered-MoS 2 flakes was demonstrated using high temperature ($1000 C) growth process of metal-organic chemical vapor deposition (MOCVD).…”
Section: Impact Of N-plasma and Ga-irradiation On Mos 2 Layer In Molementioning
confidence: 99%
“…[1][2][3][4] In addition, 2D materials such as graphene, boron nitride nanosheets, and layered transition metal dichalcogenides (TMDs) were investigated as potential buffer layers for the epitaxial growth of III-V semiconductors on foreign substrates. [5][6][7][8] The use of TMDs, in particular, layered-MoS 2 as a buffer layer attracts the potential interest of researchers to address the issues such as large lattice and thermal expansion mismatch for the growth of GaN. 9,10 Recently, GaN epitaxy on layered-MoS 2 flakes was demonstrated using high temperature ($1000 C) growth process of metal-organic chemical vapor deposition (MOCVD).…”
Section: Impact Of N-plasma and Ga-irradiation On Mos 2 Layer In Molementioning
confidence: 99%
“…For h-BN, the 2s, 2p orbitals of B and N are treated as valence. Calculation details for the adsorption energy and the Ga, Al, As and In pseudo-potentials used have been detailed in our previous study of adsorption energy of these elements on graphene [12]. Our prior studies of Al, Ga, As and In adsorption on graphene have shown that each element binds with approximately the same binding energy on to single layer and bilayer graphene; the favored binding site on the honeycomb lattice of graphene is unique to each element.…”
Section: Alternative Qvdwe Buffer Layer Materialsmentioning
confidence: 99%
“…Despite an ultrasmooth morphology of such GaAs films, the low adsorption and migration energies of gallium and arsenic atoms on graphene result in cluster-growth mode during crystallization of GaAs films at an elevated temperature. Details on the growth process and the associated physics can be found elsewhere [12].…”
Section: Introductionmentioning
confidence: 99%
“…w-GaN (001) [64] 1970 w-AlN (001) [65] 5840 h-BN (001) [66] ≈37-57 (cubic BN) graphene (001) [67] 52 (multilayer) α-Ti (001) [68] 2048 glass [69] 2000-4000…”
Section: Progress Reportmentioning
confidence: 99%